EFEKTIVITAS STIMULANSIA KOMBINASI SARI UMBI BIT DAN BUAH APEL TERHADAP KETAHANAN FISIK DAN KADAR Hb TIKUS PUTIH Sprague Dawley - Moerfiah .; Yulianita .; Deni Setiawan (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2019)
Human physical exercise is influenced by hemoglobin levels in the blood, stimulant testing of underlying fatigue should be tested for Hb levels. This study aims to determine the increase in stimulation and hemoglobin levels of white rats using beetroot and apple juice. The method used for stimulant testing was the endurance test using a rotarod and for measuring Hb levels using the sahli method with a hemometer. The data observed were the duration of resistance on rotarod stick which were rotated, the experimental animals used were 25 animals divided into 5 treatment groups with each group of 5 rats namely: group of beetroot and apple (1: 1) (2.8g: 0.63mg / 200gBB), comparison (2: 1) of (5.6g: 0.63mg / 200gBB), comparison (1: 2) of (2.8g: 1.26mg / 200gBB), negative control (-) (CMC-Na 0.5%) and positiveÂ  control (+) caffeine 20 mg / 200g BB. Dosage treatment is carried out in one day.The results showed that the combination of beetroot and apple juice had an increase in stimulant and hemoglobin levels of white rats with the most effective dose for stimulant enhancement and Hb levels were found in the second dose compared to beetroot and apple juice (2: 1) 5.6 g / 200gBB: 0.63 g / 200gBB.